Chapter Unsheathing the Katana. The Long Fortune of the First Two Japanese Embassies in Italy: Rediscovery and Rereading between Continuity and Discontinuity (1873-1905) - TRIPEPI, ALESSANDRO (Connessioni. Studies in Transcultural History, 2022)
At the end of the nineteenth century, Italy welcomed an official embassy sent by the government in Tokyo to make Japan more integrated into the new world scene it was entering. The cultural and political elites of the peninsula had the chance to discover, or rather rediscover, the charm of a world that had been lost over the centuries. This essay aims to reflect on the means and meanings of this late nineteenth-century encounter. Indeed, from this moment onwards, Japan increasingly became part of Italian mental horizons, in particular through the rereading and reuse of two precedents dating back to the sixteenth and seventeenth centuries that saw the two countries dialogue and "discover" each other for the first time.